(untitled) (Development Service Industry Management, 2025)
The article examines modern hospitality models used in the international hotel and restaurant business, their essence, features and impact on improving the quality of service. The author emphasizes the relevance of the topic in the context of global competition, changing consumer preferences and the rapid introduction of technological innovations in the hospitality industry. Particular attention is paid to the analysis of key hospitality concepts. The article reveals in detail their characteristics, advantages, as well as practical aspects of implementation in the work of international hotel chains. Based on the research conducted, recommendations have been developed for the implementation of these models in the activities of hotel and restaurant businesses. These recommendations are aimed at increasing guest satisfaction, forming customer loyalty, improving reputation and strengthening competitive positions in the international market. At the end of the article, the importance of a comprehensive approach to the implementation of modern hospitality models is emphasized, and the prospects for further research related to the adaptation of innovative solutions to market conditions and cultural characteristics of target audiences are indicated. The article used research methods such as the study and analysis of professional literature, comparison of various modern concepts of hospitality, and generalization of best practices of international hotel and restaurant chains. The use of these methods allowed to gain a deeper understanding of existing approaches, identify key features and trends in the industry, and suggest practical ways to implement effective service models.